KAJIAN PSIKOPRAGMATIKCERITA YONG DOLAH - Maszurah Zulkarolina; M. Nur Mustafa; Syafrial Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This research about Psychopragmatic Study of Yong Dolah Story. This research is motivated by folktale with a story style in a special Melayu community which is a humorous story or anecdotal story that is closely related to its readers, one of them is a high school/ majors/ equivalent student. The anecdotal story isYong Dolah Story. The purpose of this study is to get students 'understanding of the stories discussed by psychopragmatics or the readers' psychology of the stories. The research method used is descriptive qualitative. Data collection techniques using literature study techniques, questionnaires, and interviews as data reinforcement. Techniques of respondent data analysis were obtained from questionnaire data collection, then interviews to get a psychopragmatic picture of Yong Dolah story readers. The results of research on Yong Dolah's children from the seven aspects of Assessment, so they can accept the Yong Dolah story as an anecdotal text story used in learning Indonesian.KeyWords: Psychopragmatic, Anecdotal Story, Yong DolahStory